Statistics review 3: Hypothesis testing and P values - Whitley, Elise (BioMed Central, 2002)
The present review introduces the general philosophy behind hypothesis (significance) testing and calculation of P values. Guidelines for the interpretation of P values are also provided in the context of a published example, along with some of the common pitfalls. Examples of specific statistical tests will be covered in future reviews.